1994
DOI: 10.1142/s0218348x94000442
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Image Compression

Abstract: This paper begins by presenting a simple explanation of the main ideas in fractal image compression. It then presents a brief discussion of the current state of the art along with some results comparing fractal encoding, JPEG, and a wavelet scheme. The conclusion contains references to many of the latest theoretical and implementation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 0 publications
2
56
0
5
Order By: Relevance
“…For example, for each range block R i we could consider a number of domain blocks, possibly weighting each block inversely according to the collage error that it yields. The idea of using multiple domain blocks in order to improve the accuracy of approximation has been around for some time (see, for example, [9]). However, S. Alexander [1] has recently shown that this idea can be used effectively for purposes other than simply increasing the PSNR, for example, denoising, edge detection and block classification.…”
Section: Evolution For a Convex Combination Of Contraction Mappingsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, for each range block R i we could consider a number of domain blocks, possibly weighting each block inversely according to the collage error that it yields. The idea of using multiple domain blocks in order to improve the accuracy of approximation has been around for some time (see, for example, [9]). However, S. Alexander [1] has recently shown that this idea can be used effectively for purposes other than simply increasing the PSNR, for example, denoising, edge detection and block classification.…”
Section: Evolution For a Convex Combination Of Contraction Mappingsmentioning
confidence: 99%
“…Indeed, such selfsimilarity properties inspired the seminal paper of M. Barnsley and S. Demko on "iterated function systems" and the inverse problem of fractal construction [4] which, in turn, led to intensive investigations into fractal image coding and compression [3,5,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the vector quantization [1], fractal image compression [2], wavelet image compression [3], and block truncation coding (BTC) [4]. In this study, we focus on the last one.…”
Section: Introductionmentioning
confidence: 99%
“…In fractal image compression [11], the self-similarity between different parts of an image is used for image compression based on contractive mapping fixed point theorem. However, the fractal image compression focuses on contractive transform design, which makes it usually not suitable for lossless image compression.…”
mentioning
confidence: 99%